Effects of Brief Depression and Anxiety Management Training on a US Army Division's Primary Care Providers. Issue 5 (28th January 2020) - Amin, Rohul; Thomas, Mary Ann
Abstract: Introduction: There is a nation-wide gap between the prevalence of mental illness and the availability of psychiatrists. This places reliance on primary care providers (PCPs) to help meet some of these mental health needs. Similarly, the US Army expects its PCPs to be able to manage common mental illnesses such as anxiety and depression. Therefore, PCPs must be able to close their psychiatric skills gaps via lifelong learning. Materials and Methods: Following needs assessment of PCPs in a US Army division, the curriculum was developed. Objectives targeted pharmacological management of depression and anxiety. Behavioral intervention skills were also taught to treat insomnia. Didactics and case-based small groups were used. A novel psychotropic decisional tool was developed and provided to learners to assist and influence their future psychiatric practice. Pre-training, immediate post-training, and 6-month assessments were done via survey to evaluate confidence and perceived changes in practice. The curriculum was executed as a quality improvement project using the Plan, Do, Study, Act framework. Results: Among 35 learners, immediate confidence in selecting optimal psychotropic and perceived knowledge, skill to change the dose or type of medication, and confidence in prescribing behavioral sleep improved significantly with large effect sizes. At 6-month follow-up, learners reported that they were more likely to adjust medications for anxiety or depression and were more likely to start a new medication for anxiety or depression because of the training with moderate effect sizes. Use and satisfaction with the psychotropic decisional tool are also reported. Conclusions: Our psychotropic decisional tool illustrates a novel algorithmic approach for operationalizing the management of depression and anxiety. Similar approaches can improve the skills of a variety of PCPs in the management of psychiatric disorders. Further studies in the military operational setting are needed to assess the effects of similar educational interventions on access to behavioral health care, suicidal behaviors, and unit medical readiness.